التبادل الدلالي بين صيغة اسم الفاعل وصيغ صرفية أخرى في قراءة حمزة ورواية حفص - عمرو حمدي إبراهيم خاطر; محمد سعد محمد السيد; محمد محيي الدين أحمد (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2022)
إن الاختلافَ القالبي في صِيغ المادَّة الواحِدة راجعٌ إلى تَعدُّد ضروبِ معانيها المتنوِّعة، ومن هذه الصيغ اسم الفاعل، فهو يدل على الذات والحدث، بينما يدل الفعل على الزمن والحدث، كما أن اسم الفاعل يدل على ثبوت الوصف في الزمن الماضي واستمراره، بخلاف الفعل الماضي الذي يدل على وقوع الفعل في الزمان الماضي لا على ثبوته واستمراره، ، وعلى سبيل المثال للتبادل بين صيغة (فاعل) مع غيرها: التبادل بين اسم الفاعل على صيغة (فاعِل) و (فَعِل)، فهما صيغتان تتشابهان من عدة جوانب، فصيغة (فَعِل) تكون اسما كقولهم: كَتِف و كَبِد، وتكون صفة كقولهم: حَذِر ووَجِع، و(فاعل) أيضا تكون اسمًا كقولهم: كاهِل وغارِب، وتكون صفة كذلك كقولهم: ضارب و كاتب وغيرها. وعندهم أنَّ عنصرًا لُغويًّا مثل (عالم) يختلف دَلاليًّا عن عنصرٍ مثل (علام)، وهُما بدورهما مختلفانِ عن عنصرٍ مثل(عليم)، و(معلوم)، وغيرها. إن القراءات القرآنية المتضمنة اختلافات صرفية قد تؤدي إلى تغير في المعنى من قراءة لأخرى، مع ملاحظة أن هذا الاختلاف في المعنى ليس خلاف تناقض، وإنما خلاف تنوع في الفهم أو المعنى بما يزيد من وضوح المراد وتأكيده. Abstract        The modal difference in the formulas of the same word is due to the multiplicity of its various meanings, and among these formulas is the Participle. It indicates the subject and the event while the verb indicates the time and the event. Moreover, the Participle indicates the persistence of the description in the past tense and its continuity, unlike the past verb, which indicates the occurrence of the verb in the past tense, not its persistence and continuity. For example, to exchange between the form fa’el with another: the exchange between the Participle on the form fa’el and fae’l, they are similar in many aspects. The form fae’l can be a noun as they say: shoulder (Katef) and liver (Kabed), and an adjective as they say: aware (Ḥadhr) and agonized (Waje’). The form fa’el also can be a noun as they say: nape (Kaḥil) and ridge (Gharib), and an adjective as they say: hitter (Ḍarib), writer (Kattib) and others. According to them, a linguistic element such as Scholar (‘Alim) is semantically different from an element such as Expert (‘Allam), and they, in turn, are different from an element such as learned (‘Alim), known (Ma’loum), and others. The Qur’anic readings that include morphological differences may lead to a change in meaning from one reading to another, noting that this difference in meaning is not a contradiction, but rather a difference in understanding or meaning, which increases the clarity and confirmation of the intended.